Effect of MELT method on thoracolumbar connective tissue: The full study. Issue 1 (January 2017) - Sanjana, Faria; Chaudhry, Hans; Findley, Thomas
Summary: Altered connective tissue structure has been identified in adults with chronic low back pain (LBP). A self-care treatment for managing LBP is the MELT method. The MELT method is a hands-off, self-treatment that is said to alleviate chronic pain, release tension and restore mobility, utilizing specialized soft treatments balls, soft body roller and techniques mimicking manual therapy. The objective of this study was to determine whether thickness of thoracolumbar connective tissue and biomechanical and viscoelastic properties of myofascial tissue in the low back region change in subjects with chronic LBP as a result of MELT. This study was designed using a quasi experimental pre–post- design that analyzed data from subjects who performed MELT. Using ultrasound imaging and an algorithm developed in MATLAB, thickness of thoracolumbar connective tissue was analyzed in 22 subjects. A hand-held digital palpation device, called the MyotonPRO, was used to assess biomechanical properties such as stiffness, elasticity, tone and mechanical stress relaxation time of the thoracolumbar myofascial tissue. A forward bending test assessing flexibility and pain scale was added to see if MELT affected subjects with chronic LBP. A significant decrease in connective tissue thickness and pain was observed in participants. Significant increase in flexibility was also recorded.